Against the stream: early diagnosis of dementia, is it so desirable?. (4th January 2019) - Brayne, Carol; Kelly, Sarah
Summary: The Prime Minister's challenge on dementia called for improved dementia diagnosis rates, based on assumptions of benefit to individuals and those who care for them. Subsequent policies have led to increased target drives for clinical practice to achieve early diagnosis of dementia through intense case identification. However, the current evidence base and treatment options do not support screening for dementia, and there is little empirical evidence that such intensive case identification and early diagnosis for dementia is justified without a better understanding of the benefits, costs and potential harms to individuals and services. Declaration of interest: None.